Performance supply chain management on construction site : a research proposal / Shahela Mamter, Wan Nur Azma Izzati Wan Amran and Mohd Esham Mamat - Mamter, Shahela; Wan Amran, Wan Nur Azma Izzati; Mamat, Mohd Esham (2012)
In general, the term 'supply chain' is used to describe the linkage of companies that turns a series of basic materials, products or services into a finished product for the client. But in the construction industry, a supply chain comprises the network of organizations involved in the different processes and activities which produce the materials, components and services that come together to design, procure and deliver a building. The purpose of this research are to explore the performance of construction supply chain on construction sites and also to investigate the wastages and problems found caused by parties involved in the supply chain. The research employed a mixed mode approach, implemented through literature review, informal interviews and questionnaire survey, to analyze the performance and to access the implementation of supply chain management on construction sites. This research will produce better collaborative relationships and also establish long term relationships among all members of the supply chain. The research aims to achieve a more successful cost management and better delivery of good underlying value to the client.